Determination of Toxicity and Hazard Levels of Fluorides in Laboratory Animals - Ibragimov, Ahmad Tulkinovich; Khujamqulov, Suxrob (American Journal of Biomedicine and Pharmacy, 2026)
This scientific article presents the determination of toxicity and hazard levels resulting from the chronic exposure of white mice to sodium fluoride solutions of varying concentrations over a period of three months. Based on the analysis of experimental data, it was established that sodium fluoride exhibits a high level of toxicity in the organism of white mice.